Cathodic generation of hydrogen peroxide sustained by electrolytic O2 in a rotating cylinder electrode (RCE) reactor. (1st February 2022) - Cornejo, Oscar M.; Sirés, Ignasi; Nava, José L.
Highlights: Novel (C-PTFE)-coated ccloth as rotating cylinder electrode (RCE) to produce H2 O2 . No use of air pump: O2 formed at Ti|IrO2 anodes is reduced at the rotating cathode. The rotation of RCE favors mass transport of O2 and enhances the H2 O2 accumulation. Dissolved atmospheric air by suction favors the H2 O2 electrosynthesis at slow rotation. Bulk electrolysis: 177.2 mg L   −   1 H2 O2 at the fastest rotation, with 0.013 kWh (gH2 O2 ) −1 . Abstract: This investigation reports the electrosynthesis of H2 O2 from the two-electron reduction of dissolved O2, provided by anodic water oxidation, in a rotating cylinder electrode (RCE) reactor. O2 evolved at six surrounding Ti|IrO2 anode plates, whereas the oxygen reduction reaction (ORR) occurred at a (C-PTFE)-coated carbon cloth covering a rotating steel cathode. The mass transport characterization of the cathodic ORR to yield H2 O2 was carried out through limiting current measurements (-0.65 ≤  E ≤ -0.3 V vs. SHE). Peripheral velocities ( U ) between 11.9 and 79.6 cm s − 1 (i.e., Reynolds ( Re ) numbers of 4537 ≤ Re ≤ 30243) were employed to ensure turbulent flow conditions. An apparent plateau was obtained in the studied potential range, in agreement with mass transport-controlled ORR. From the limiting current values obtained, the mass transport correlation k m a = b U c, which describe the transport considering the geometrical aspects of the cell and the hydrodynamic regime, were obtained. Additionally, bulk electrolyses were executed to accumulate H2 O2, with no O2 feeding from any air pump. These trials were performed under mass transport control at a cathode potential of -0.46 V vs. SHE. Both, mass transport studies and bulk H2 O2 electrogeneration, were performed in the presence and absence of atmospheric air on top of the RCE reactor to evaluate the potential contribution of additional O2 dissolution promoted by the electrolyte velocity and pressure gradients imposed by the RCE. Its contribution to H2 O2 production depended on U . The best conditions for the self-sustained electrolytic H2 O2 synthesis were U  = 79.6 cm s − 1 and cathode potential of -0.46 V, achieving 177.2 mg L − 1 H2 O2 with current efficiency and energy consumption of 23.3% and 0.013 kW h (g H2 O2 ) −1 after 180 min. The potential application of this RCE reactor to the degradation of organic pollutants is thus envisaged.